Calculations in pharmacy - Rouse, Sue H.; Webber, M. George (Philadelphia, Pennsylvania : J. B. Lippincott Company, 1975)
Since this textbook was first printed there have been a great many changes in pharmaceutical education, and to accommodate newer concepts, much of the emphasis on "the art of compounding" has been reduced or neglected in favor of orientation toward patients.
1. Basic mathematics review -- 2. Weights and measures -- 3. Reducing and enlarging formulas -- 4. The relationship of systems -- 5. Percentage preparations -- 6. The calculation of doses -- 7. Density, specific gravity and specific volume -- 8. Additional calculations pertaining to the strength of preparations -- 9. Ratio strength, triturations and stock solutions -- 10. Concentration and dilution -- 11. Temperature conversion -- 12. Commercial calculations -- 13. Isotonic solutions -- 14. Chemical calculations relating to the practice of pharmacy.
Keywords: PHARMACY